6 - The Public Dimensions of the University in Africa - Ebrima Sall, (Journal of Higher Education in Africa, 2003)
This paper’s principal purpose is to explore the range of ways in which African universities act as public institutions—i.e., how both are shaped by and influ- ence the social, political, and economic contexts in which they are situated. In particular, we consider the multiple dimensions, often resulting in tensions in contexts of poverty and instability, of the African university as an actor in politics, civil society, and the public sphere AND as a key institution in the expectations and the strategies of a range of actors, groups, and constituencies.